2001
DOI: 10.1046/j.1439-0418.2001.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐plant preference and oviposition responses of the sorghum midge, Stenodiplosis sorghicola (Coquillett) (Dipt., Cecidomyiidae) towards wild relatives of sorghum

Abstract: Sorghum midge, Stenodiplosis (Contarinia) sorghicola (Coquillett) is an important pest of grain sorghum world-wide. Considerable progress has been made in screening and breeding for resistance to sorghum midge. However, some of the sources of resistance have become susceptible to sorghum midge in Kenya, in eastern Africa. Therefore, the wild relatives of Sorghum bicolor were studied as a possible source of new genes conferring resistance to sorghum midge. Midge females did not lay eggs in the spikelets of Sorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…No direct comparison was made of responses to synthetic blends and the natural stimulus (Birkett et al, 2004). Sharma and Franzmann (2001a) showed that C. sorghicola responded to color and odor of host plants, and also demonstrated differential oviposition on various wild relatives of sorghum (Sharma and Franzmann, 2001b).…”
Section: Responses Of Cecidomyiid Midges To Host Plant Volatilesmentioning
confidence: 99%
“…No direct comparison was made of responses to synthetic blends and the natural stimulus (Birkett et al, 2004). Sharma and Franzmann (2001a) showed that C. sorghicola responded to color and odor of host plants, and also demonstrated differential oviposition on various wild relatives of sorghum (Sharma and Franzmann, 2001b).…”
Section: Responses Of Cecidomyiid Midges To Host Plant Volatilesmentioning
confidence: 99%
“…The high genetic diversity could potentially be exploited in broadening the genetic base of sorghum breeding germplasm, while the unique diversity imply that wild sorghum is a potential source of novel genes such as pests and disease resistance. The genetic potential of wild relatives of sorghum, particularly as sources of resistance to pests and diseases, is well documented such as for sorghum shoot fly (Kamala et al 2009), sorghum midge (Sharma and Franzmann 2001), green bug (Duncan et al 1991), downy mildew (Kamala et al 2002) and ergot (Reed et al 2002). Moreover, the substantial genetic variability and differentiation revealed in sorghum landraces of Kenya should be incorporated in breeding programs by developing different populations with a broad genetic base.…”
Section: Implications For Utilization and Conservation Of Germplasmmentioning
confidence: 99%
“…The potential of wild sorghum to provide new sources of resistance and adaptation in breeding programs have been established (Sharma and Franzmann 2001;Gurney et al 2002;Kamala et al 2002;Rao Kameswara et al 2003) but only partially explored. Conversely, crop-to-wild gene flow could result in the spread of genes from both domesticated and transgenic varieties into wild populations, and possible subsequent creation of aggressive weeds or invasive plants (Ellstrand et al 1999;Conner et al 2003), depending on the characteristics of the introgressed genes.…”
Section: Introductionmentioning
confidence: 99%